Efektivitas Penggunaan Terapi Akupunktur Metode Korean Hand Therapy pada Lansia dengan Nyeri Muskuloskeletal di Posyandu Lansia Poltekkes Kemenkes Surakarta - Joko Tri Haryanto; Listina Ade Widya Ningtyas (Poltekkes Kemenkes Surakarta, 2020)
Background: Disorders of the musculoskeletal system can affect the functions of the body's movers consisting of bones, muscles, cartilage, tendons, ligaments and other connective tissue. Acupuncture therapy began to develop with various types of micro acupuncture that began to be widely applied, such as the Korean Hand Therapy technique. The purpose of this study was to analyze the effectiveness of acupuncture methods or techniques in elderly patients who experience musculoskeletal pain. Methods: This type of research is Quasi Experimental. The location of the study was at the Posyandu Elderly Ngemplak Boyolali in March-May 2019. The population is elderly musculoskeletal pain by 50 people. A sample of 30 people was divided into 3 treatment groups. Data analysis using the Anova Test. Results: Significance results> 0.05 so it can be concluded that Ho is accepted, Ha is rejected, meaning there is no difference in the method of therapy in reducing pain. Conclusion: The Most Effective Method for Overcoming Musculoskeletal Pain in this Study There was no difference between the Acupuncture Therapy Group, the Korean Hand Therapy Group and the Combined Acupuncture Therapy Group and the Korean Hand therapy.